The Speed Reading Book : Read More, Learn More, Achieve More - Buzan, Tony (London Pearson, 2010)
Tony Buzan presents information about your eyes and brain that will improve all aspects of your reading and proves that reading speeds of over 1000 words per minute are possible.
Include Index
Keywords: Speed reading